Microscopic and PCR-based detection of microsporidia spores in human stool samples = Detección microscópica y molecular de esporas de microsporidios en muestras de heces humanas - Mena, Cristian Javier; Barnes, Andrés; Castro, Gonzalo; Guasconi, Lorena; Burstein, Verónica Liliana; Beccacece, Ignacio; Paulin, Patricia Catalina; Arneodo Larochette, Joel Demian; Carnevale, Silvana; Astudillo, Germán; Cervi, Laura; Theumer, Martín Gustavo; et al. (Elsevier, 2020)
Microsporidia are obligate intracellular fungi with a remarkable ability to infect a wide range of invertebrate and vertebrate hosts. Namely, Enterocytozoon bieneusi is the most frequently microsporidia reported worldwide, and mainly associated with chronic diarrhea and wasting syndrome in AIDS patients. Microscopy and PCR-based detection techniques are effective for diagnosis and identification of species and genotypes; however, these methods should be standardized in each laboratory. In this study, we performed microscopy and nested PCR techniques with PCR product sequencing to detect E. bieneusi in human stool samples. These techniques, if applied together, might prove useful for diagnosis and future epidemiological studies of intestinal microsporidiosis in Argentina.